KAJIAN ALIRAN MELALUI PELIMPAH AMBANG LEBAR DAN PELIMPAH AMBANG TIPIS - Risman, Risman; Warsiti, Warsiti (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2013)
In order to be an effective management of irrigation water, the flow rate should be measured in the upstream primary channels, the branch line and the tapping tertiary buildings. However, to simplify the management of irrigation network have only a few building types that may be used in irrigation areas. This study is limited to measure rate of flow through the spillway sillwidth with a round shape and spillway sill lighthouse thin rectangular. The methodology used was tested in the laboratory by varying the flow hydraulics start of Q1, Q2, Q3, ..., Qn, to get the water level variations in the upstream and the downstream in spillway is constan, which can be obstained with the relationship between the discharge water level in the upstream and downstream of the spillway. Besides, it was also found the relationship of the variation of the discharge flowed through the sill wide spillway and thin threshold to high energy lost occurs. From the results of this research, the relationship with the discharge water level in the upstream, downstream water level, water level above the threshold, and the threshold energy loss for the overflow width spillway and thin sill have a similar trend. To spillway width threshold produces less energy loss than the spillway sill thin with trend Y = - 405,6 X2 ? 11,99 X ? 0,001 for sill width spillway and Y = 1,183 X 0,552 for the overflow thin threshold with Y is the loss energy in meters and X in discharge in m3/s.